Identifying cardiorespiratory neurocircuitry involved in central command during exercise in humans. - Green, A; Wang, S; Purvis, S; Owen, S; Bain, P; Stein, J; Guz, A; Aziz, T; Paterson, D (2007)
For almost one hundred years, the exact role of human brain structures controlling the cardiorespiratory response to exercise ('central command') has been sought. Animal experiments and functional imaging studies have provided clues, but the underlying electrophysiological activity of proposed relevant neural sites in humans has never been measured. In this study, local field potentials were directly recorded in a number of 'deep' brain nuclei during an exercise task designed to dissociate the exercise from peripheral feedback mechanisms. Several patient groups had electrodes implanted sterotaxically for the treatment of movement disorder or chronic pain. Fast Fourier transform analysis was applied to the neurograms to identify the power of fundamental spectral frequencies. Anticipation of exercise resulted in increases in heart rate, blood pressure and ventilation. The greatest neural changes were found in the periaqueductal grey area (PAG) where anticipation of exercise was accompanied by an increase of 43% in the power of the 12-25 Hz frequency band (P = 0.007). Exercise increased the activity by 87% compared to rest (P = 0.006). Changes were also seen in the 60-90 Hz band when anticipation or exercise increased power by 32% (P = 0.006) and 109% (P < 0.001), respectively. In the subthalamic nucleus there was a reduction in the power of the beta frequency during both anticipation (7.6 +/- 0.68% P = 0.001) and exercise (17.3 +/- 0.96% P < 0.001), whereas an increase was seen with exercise only at higher frequencies (93 +/- 1.8% P = 0.007). No significant changes were seen in the globus pallidus during anticipation of exercise. We provide direct electrophysiological evidence highlighting the PAG as an important subcortical area in the neural circuitry of the cardiorespiratory response to exercise, since stimulation of this structure is known to alter blood pressure in awake humans.